Involvement of salicylic acid in the resistance responses of different wheat cultivars to two Russian wheat aphid biotypes - Tsai, Yi-Hsiu (University of the Free State, 2011)
The effect of the Russian wheat aphid (RWA) (Diuraphis noxia, Kurdjumov), South African biotype 1 (RWASA1) and biotype 2 (RWASA2) infestation, on signalling events, with emphasis on salicylic acid (SA), in different resistant wheat (Triticum aestivum L.) cultivars, containing Dn1 (Tugela DN) and Dn5 (PAN 3144) resistant genes, was investigated. This study was mainly conducted in an attempt to compare changes in SA content and factors affecting it during the resistance response of different wheat cultivars towards RWASA1 and RWASA2 infestation. SA contents were determined by high performance liquid chromatography (HPLC). To obtain insight into SA metabolism during the resistance responses the involvement of phenylalanine ammonia lyase (PAL), isochorismate synthase (ICS), SA UDP-glucosyl transferase (SAGT) and SA binding protein catalase (CAT) were investigated. In addition, lipoxygenase (LOX) activities, related to the synthesis of the signalling molecules, jasmonates and oxylipins, were determined during the resistance responses. PAL, CAT and LOX activities were assayed spectrophotometrically while ICS and SAGT mRNA expression was measured on a molecular level, using reverse transcriptase quantitative polymerase chain reaction (RT-qPCR). The resistance responses during the incompatible interactions, RWASA1-Dn1, RWASA1-Dn5 and RWASA2-Dn5 were characterized by an earlier and higher induction of total SA (total of free and conjugated forms). In contrast, in the compatible RWASA2-Dn1 interaction, a much later and lower induction of SA accumulation was found. In addition, the level of SA induction during the Dn5 resistance response was higher than during the Dn1 resistance response. Furthermore, RWASA1 infestation of Dn5 resistant wheat caused a higher SA induction than that of RWASA2 infestation. These results reflect a correlation between the level of SA accumulation and the resistance level. Increases in PAL activity and not significant expression of ICS indicate that the phenylpropanoid pathway for SA synthesis was preferred over the isochorismate pathway during the resistance responses towards both RWA biotypes. Increased free SA contents were accompanied by increased SAGT expression and conjugated SA contents, indicating that free SA was mainly synthesized de novo and further metabolised in the conjugation reactions catalyzed by SAGT. The finding that increased free SA contents were accompanied by inhibition of CAT activities during RWA-wheat interactions is consistent with SA signalling transduction via increased H2O2 levels. However, the inhibition patterns of CAT activity were also different in RWASA1 and RWASA2 infested resistant cultivars. Significant induction of LOX activities occurred before the accumulation of SA in the incompatible RWA-wheat interactions. This may point to an early defence function of LOX, upstream from SA, which may include the production of signal molecules such as oxylipins. The levels of LOX induction were consistent with resistance against the two RWA biotypes. The involvement of SA, PAL, SAGT, CAT and LOX in both Dn1 and Dn5 resistance responses towards infestation by both RWA biotypes is indicative of the similarity between different RWA-wheat interactions. However, differences in the timing, level and pattern of changes occurred. The fact that Dn1 resistance was overcome by RWASA2 and that Dn5 resistance is effective against both RWA biotypes was clearly illustrated by results of this study.
Dissertation (M.Sc. (Plant Sciences))--University of the Free State, 2011
Keywords: Wheat -- Diseases and pests; Wheat -- Insect resistance; Russian wheat aphid; Salicylic acid; Catalase; Lipoxygenase; Salicylic acid UDP-glucosyl transferase; Isochorismate synthase; Phenylalanine ammonia lyase